Model prediksi perkembangan kawasan wisata Bali utara ditinjau dari variabel tata guna lahan dan infrastruktur - Dewa Ayu Nyoman Sriastuti; Putu Alit Suthanaya; Dewa Made Priyantha Wedagama; Anak Agung Gede Yana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
Bali is one of the provinces included in the 50 National Tourism Destinations (NTD) which has been developed into 5 Regional Tourism Destinations (RTD) which are supported by Regional Tourism Strategic Areas (RTSA) with a tourism theme. This research aims to examine tourism development by considering the influence of tourism components which are reflected in land use variables and transportation infrastructure components, using the North Bali RTD supported by RTSA Lovina and RTSA Air Sanih as the research location. This research makes a positive contribution to regional economic growth and community welfare and the research output is expected to provide input and information for the region in its efforts to increase the development of tourist areas in North Bali. Data were collected by distributing questionnaires to 100 tourists, using the PLS-SEM analysis method. The research results show that tourism development in North Bali can be predicted significantly through land use and transportation infrastructure variables with a contribution of 63.4%, where the transportation infrastructure variable has a more significant influence, namely 65.7%, than the land use variance of 19%. Meanwhile, land use contributes 70.4% to transportation infrastructure.